Effects of different protein diets on growthand food conversion ratio of postlarvae ofMacrobrachium rosenbergii (deMan) - Felix, N; Jayaseelan, M J Prince (Indian Journal of Fisheries, 2011)
The experiment was designed to study the effect of different protein levels onthe survival and growth of Macrobrachium rosenbergii in nursery phase. Theexperiment was conducted for 45 days in plastic tubs of 20 L capacity by stockingten postlarvae weighing 0.015 to 0.018g. Seven diets were formulated at differentprotein levels of 15, 20, 25, 30, 35, 40 and 45% using the same ingredients. Theprawn reared on 40% protein diet exhibited best performance in terms of growthfollowed by those on 45 and 35% protein diets.Â  However, the high proteinefficiency ratio (PER) was recorded in the diet that contained 15% protein.